The Effect of Motivation and Organizational Climate on Specialist Doctors’s Loyalty in Prima Medan Royal Hospital - Mulya; Tan Suyono; Ali Napiah Nasution; Adek Amansyah (CV. Inara, 2022)
The role of specialist doctors in hospital services is large, making the bargaining position of specialist doctors high against hospitals. Various literature states that loyalty plays an important role in the formation of a person's decision in choosing a place of work and giving commitment. This study analyzes the effect of motivation and organizational climate on the loyalty of specialist doctors. This explanatory survey research uses a cross-sectional design. The study was conducted at the Royal Prima General Hospital Medan for 1 (one) month starting from July 2021 to August 2021. The sample was 50 people who were determined by the inclusion criteria were specialist doctors who had worked for at least 2 years. Data were analyzed using the Chi-Square test and multiple logistic regression. The results of statistical tests using Chi-Square show that motivation has a significant effect on the loyalty of specialist doctors, whereas the results of statistical tests show that physical and esteem needs have a p-value of less than 0.05. The organizational climate also affects the loyalty of specialist doctors, where the results of statistical tests show that flexibility, responsibility, standards, and commitment have p values less than 0.05. The results of the multiple logistic regression test show that the variable that has the greatest influence on the loyalty of specialist doctors is flexibility. With an Exp (B) value of 18,444 (95%CI 2,052- 165,779), Respondents who stated good flexibility had 18 times more loyal than those who stated poor flexibility. In conclusion, good flexibility will increase the loyalty of specialist doctors. This study concludes that motivation and organizational climate have a significant effect on the loyalty of specialist doctors. The aspect of flexibility in the organizational climate has the most influence on the loyalty of specialist doctors.